EFEITOS DE GIBERELINA E ETHEPHON NO DESENVOLVIMENTO DE CULTIVARES DE SORGO SACARINO - Pereira, MÃ¡rcio; Castro, Paulo R. C.; Scandiuzzi, Eduardo (REVISTA DE AGRICULTURA, 2015)
EFEITOS DE GIBERELINA E ETHEPHON NO DESENVOLVIMENTO DE CULTIVARES DE SORGO SACARINO